Creative Women in Medieval and Early Modern Italy : a Religious and Artistic Renaissance - Coakley, John.; Matter, E. Ann. (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.
Frontmatter -- Contents -- List of Illustrations -- Preface and Acknowledgments -- 1. Introduction: Women's Creativity in Religious Context -- Part I: Women's Religious Expression: Thirteenth to 17 Fifteenth Centuries -- 2. The Feminine Mind in Medieval Mysticism -- 3. The Authorial Role of Brother A. in the Composition of Angela of Foligno's Revelations -- 4. Women and the Production of Religious Literature in the Vernacular, 1300-1500 -- 5. Urban Spaces, Women's Networks, and the Lay Apostolate in the Siena of Catherine Benincasa -- 6. Chiara Gambacorta of Pisa as Patroness of the Arts -- Part II: Women's Religious Expression: Sixteenth and 155 Seventeenth Centuries -- 7. Piety and Patronage: Women and the Early Jesuits -- 8. Per Speculum in Enigmate: Failed Saints, Artists, and Self-Construction of the Female Body in Early Modern Italy -- 9. The Commentary on the Rule of Clare of Assisi by Maria Domitilla Galluzzi -- 10. The Mystic Humanism of Maria Maddalena de' Pazzi (1566-1607) -- 11. Ursula and Catherine: The Marriage of Virgins in the Sixteenth Century -- Part III: Women's Artistic Expression: Sixteenth and Seventeenth Centuries -- 12. Suor Maria Clemente Ruoti, Playwright and Academician -- 13. The Making Of Lucrezia Orsina Vizzana's Componimenti Musicali (1623) -- 14. Four Views of Milanese Nuns' Music -- Notes on the Contributors -- Index of Modern Authors -- General Index -- Backmatter
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Dec. 09, 2016).
JSTOR
Keywords: Women in Christianity -- Italy -- History -- Congresses; Women -- Italy -- History -- Middle Ages, 500-1500 -- Congresses; Women -- Italy -- History -- Renaissance, 1450-1600 -- Congresses; Sex role -- Religious aspects -- Christianity -- History of doctrines -- Congresses; Italy -- Intellectual life -- Congresses; Italy -- Church history -- Congresses; Femmes dans le christianisme -- Italie -- Histoire -- Congrès.; Femmes -- Italie -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Femmes -- Italie -- Histoire -- 1450-1600 (Renaissance) -- Congrès.; Rôle selon le sexe -- Aspect religieux -- Christianisme -- Histoire des doctrines -- Congrès.; Italie -- Vie intellectuelle -- Congrès.; Italie -- Histoire religieuse -- Congrès.; HISTORY -- Europe -- Italy; Intellectual life; Sex role -- Religious aspects -- Christianity -- History of doctrines; Women in Christianity; Women -- Middle Ages; Women -- Renaissance; Italy; 500-1600; Church history; Conference papers and proceedings; History